Surgical Approaches to Resection of Olfactory Groove Meningiomas: Comparative Meta-analysis of the Endoscopic Endonasal versus Transcranial and Unilateral versus Bilateral Approaches - Brown, Nolan J.; Pennington, Zach; Patel, Saarang; Kuo, Cathleen; Chakravarti, Sachiv; Bui, Nicholas E.; Gendreau, Julian; Van Gompel, Jamie J. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Introduction Here we systematically review the extant literature to highlight the advantages of bilateral versus unilateral approaches and endoscopic endonasal (midline) approaches versus transcranial approaches for olfactory groove meningiomas, focusing on complications, extent of resection, and local recurrence rates.Methods Three databases were queried to identify all primary prospective trials and retrospective series comparing outcomes following endoscopic endonasal versus transcranial approaches and unilateral versus bilateral craniotomy for surgical resection of olfactory groove meningiomas. All articles were screened by two independent authors and selected for formal analysis according to predefined inclusion/exclusion criteria.Results Seven studies comprising 288 total patients (mean age 55.0 ± 24.6 years) met criteria for inclusion. In the three comparing the endoscopic endonasal (n = 21) versus transcranial (n = 32) approaches, there was no significant difference between the two with respect to gross total resection (p = 0.34) or rates of Simpson Grade 1 resection (p = 0.69). EEA demonstrated higher rates of overall complications (p < 0.01) including postoperative infection (p = 0.03). In the four studies comparing bilateral (n = 117) versus unilateral approaches (n = 118), overall complication rates (p < 0.01) and disease recurrence (p = 0.01) were higher with bilateral approaches. All surgery-related mortalities also occurred in the bilateral cohort (n = 7, 7.14%). Gross total resection (p = 0.63) and Simpson grade (p = 0.48) were comparable between approaches. Olfaction preservation was superior for unilateral approaches (p < 0.01).Conclusions Though the literature is limited, current evidence suggests that the endoscopic endonasal approach may be favorable over conventional craniotomy for select olfactory groove meningioma patients. Where craniotomy is used, unilateral approaches appear to reduce complications and the risk of olfaction loss.
Keywords: olfactory groove meningioma; anterior skull base; endoscopic endonasal; transcranial; anosmia; cerebrospinal fluid; pterional